Comparison of Functional Outcomes After Arthroscopic Rotator Cuff Repair Between Patients With Traumatic and Atraumatic Tears. Issue 10 (25th October 2022) - Godshaw, Brian M.; Hughes, Jonathan D.; Boden, Stephanie Ann; Lin, Albert; Lesniak, Bryson P.
Background: The role of tear etiology in outcomes after rotator cuff repair is not well understood. Purpose/Hypothesis: The purpose of this study was to determine the difference in outcomes after rotator cuff repair based on tear etiology. We hypothesized that traumatic rotator cuff tears will have greater improvements in functional outcome measures and range of motion (ROM) than atraumatic tears. Study Design: Cohort study; Level of evidence, 3. Methods: We conducted a chart review of 221 consecutive patients who underwent arthroscopic rotator cuff repair; prospectively collected preoperative and minimum 2-year postoperative data were evaluated. Shoulder ROM, strength, and standard shoulder physical examination findings were recorded pre- and postoperatively. Outcome measures included visual analog scale for pain, Subjective Shoulder Value (SSV), 10-item Patient-Reported Outcomes Measurement Information System (PROMIS-10; physical and mental components), and American Shoulder and Elbow Surgeons (ASES) form. Results: Of the 221 patients, 73 had traumatic tears and 148 had atraumatic/degenerative tears. There were no differences in age, body mass index, or Charlson Comorbidity Index between groups. Patients in the atraumatic cohort had significantly longer duration of symptoms before presentation (18 vs 7 months; P < .01). Preoperatively, the traumatic cohort had less motion to forward flexion (mean ± SD; 138° ± 43.7° vs 152° ± 29.8°; P = .02). Postoperatively, both groups experienced significant improvements in visual analog scale and SSV scores ( P < .001 each). However, only the traumatic cohort demonstrated improvements in ASES and PROMIS-10 physical component scores. Patients with traumatic rotator cuff tears had lower preoperative SSV and less motion than those with atraumatic tears, but they had greater improvements in SSV (40.6% ± 39.0% vs 29.2% ± 39.7%; P = .005) and forward flexion (21.6° ± 48.6° vs 2.3° ± 48.2°; P < .001), as well as strength in forward flexion, external rotation, and internal rotation ( P < .001, P = .003, and P = .002, respectively). Conclusion: Patients with traumatic rotator cuff tears have worse preoperative symptoms and more functional deficits but experience greater improvements in ROM, strength, and perceived shoulder function than those with degenerative/atraumatic tears.